Promoted interfacial charge transfer by coral-like nickel diselenide for enhanced photocatalytic hydrogen evolution over carbon nitride nanosheet. (8th January 2022) - Zhang, Xue; Xi, Chuanjun; Yue, Yuanhang; Deng, Puhui; Zhang, Linping; Hou, Yu
Abstract: Seeking an efficient and non-precious co-catalyst for g-C3 N4 (CN) remains a great demanding to achieve high photocatalytic hydrogen generation performance. Herein, a composite photocatalyst with high efficiency was prepared by modifying CN with coral-like NiSe2 . The optimal hydrogen evolution rate of 643.16 μmol g −1 h −1 is from NiSe2 /CN-5 under visible light. Superior light absorption and interfacial charge transfer properties including suppressed photogenerated carrier recombination and efficient separation of photogenerated electron-hole pairs have been observed, which account for the enhanced photocatalytic performance of CN. Graphical abstract: The NiSe2 -modified g-C3 N4 composite photocatalyst, NiSe2 /CN-5, with superior hydrogen production performance was successfully prepared. The accelerated electron transfer rate and suppressed recombination of photogenerated electron-hole pairs account for the enhanced photocatalytic activity. Image 1 Highlights: NiSe2 was fabricated on the surface of g-C3 N4 nanosheet successfully. Photocatalytic HER performance of g-C3 N4 was enhanced with NiSe2 as co-catalyst. NiSe2 /g-C3 N4 improves the light utilization and accelerates electron transfer. NiSe2 /g-C3 N4 facilitates the separation of photogenerated electron-hole pairs.